Implementation of Inadequate Home Improvement Assistance Program In Kelurahan 15, Seberang Ulu I District, Palembang City - Dinda, Tasya; Alfitri (HM Publisher, 2019)
The need for a home is one for the development of a better life, especially for poor people that which in meeting the needs of the housing is very urgent. As we known that the settlements in the middle of the city is increasingly crowded and irregular. Looking at the various considerations of population density going forward, as wel as the possibility of avoiding the formation of slum housing, it is necessary to hold a plan. This research was conducted at the public work service Cipta Karya that located at Ade Irman Nasution Street 10 Sungai Pangeran Ilir Timur I Palembang, in april 2017. The purpose of this research was to know how the implementation of assistance program for improvement to homes are not unhabitable at Kelurahan 15 Ulu Kecamatan Seberang Ulu I Palembang City. This research uses quantitative data that in the form of number or qualitative data that is suspected that uses to support research in describing the state of the focus of research. Based on the result of the analysis and discoussin that has been done before, it can be conclude that the implementation of assistance program for improvement to homes are note habitable in Palembang City by Public Works Service is conclude that has been running well. As input in this research, Public Works Service Palembang should accelerate the development of assistance program for improvement to homes are not habitable, and improve the attitude and quality of the program.